2020
DOI: 10.1021/acs.energyfuels.0c01703
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Proton Conductivity of a Zn(II)-Based MOF/Aquivion Composite Membrane for PEMFC Applications

Abstract: The membrane electrode assembly (MEA) is considered as the center of the polymer electrolyte membrane fuel cell (PEMFC); a solid electrolyte membrane is an indispensable component of MEA. For membrane research and development, reducing ohmic resistance while improving mechanical stability is a challenge. Using short-side-chain (SSC) Aquivion perfluorosulfonic acid (PFSA) dispersion and considering the theory of coordination networks, the conductivity of the Aquivion polymer electrolyte membrane is improved by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 58 publications
0
34
2
Order By: Relevance
“…In particular, the Co 2+ contained in ZIF‐67 could coordinate well with the amino group (NH 2 ) anchoring in polymer backbone, which was beneficial to improve the compactness of membrane and then enhanced the proton conductivities of membranes 26,47 . Compared to commercial Nafion117 (0.083 S cm −1 at 80°C), 24 C‐SPAEKS/HPW@MIL‐100 (Fe) 4% (0.072 S cm −1 at 80°C), 1 1 wt% ZnOx MOF‐1/Aquivion (0.035 S cm −1 at 80°C), 49 CS/UiO‐66(NH 2 )‐15 (0.056 mS cm −1 at 80°C) 50 and H 2 SO 4 @MIL‐101/CS (0.095 S cm −1 at 80°C), 51 the Am‐S‐D‐AMPS/ZIF‐67‐10% showed the highest proton conductivity (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the Co 2+ contained in ZIF‐67 could coordinate well with the amino group (NH 2 ) anchoring in polymer backbone, which was beneficial to improve the compactness of membrane and then enhanced the proton conductivities of membranes 26,47 . Compared to commercial Nafion117 (0.083 S cm −1 at 80°C), 24 C‐SPAEKS/HPW@MIL‐100 (Fe) 4% (0.072 S cm −1 at 80°C), 1 1 wt% ZnOx MOF‐1/Aquivion (0.035 S cm −1 at 80°C), 49 CS/UiO‐66(NH 2 )‐15 (0.056 mS cm −1 at 80°C) 50 and H 2 SO 4 @MIL‐101/CS (0.095 S cm −1 at 80°C), 51 the Am‐S‐D‐AMPS/ZIF‐67‐10% showed the highest proton conductivity (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…Among the commercially available equivalent weight (EW) for those membranes, 1100 (for Nafion) and 830 g/eq (for Aquivion) have been selected by many researchers due to their balanced conductivity and swelling (Figure 1), and several previous pieces of literature comparing Nafion and Aquivion focused on these materials. 18,25,[27][28][29][30] Based on SAXS results, we describe the nano-morphologies for those PFSA membranes under both dry and hydrated conditions. Moreover, the correlations between nanostructure and properties are also discussed.…”
Section: Introductionmentioning
confidence: 99%
“…On this basis, here we report the dependence of both the ionic and crystalline domains of Nafion and Aquivion on their side‐chain length. Among the commercially available equivalent weight (EW) for those membranes, 1100 (for Nafion) and 830 g/eq (for Aquivion) have been selected by many researchers due to their balanced conductivity and swelling (Figure 1), and several previous pieces of literature comparing Nafion and Aquivion focused on these materials 18,25,27‐30 . Based on SAXS results, we describe the nano‐morphologies for those PFSA membranes under both dry and hydrated conditions.…”
Section: Introductionmentioning
confidence: 99%
“…One recent example was provided by Mukhopadhyay et al [6] to fabricate nanocomposite membranes with MOFs and polymer by solution casting blending method with enhanced or better properties for fuel cell application. Another work by Paul et al [7] has shown that a novel MOF/Aquivion composite membrane exhibited enhanced proton conductivity compared with the Nafion. This material could be a promising candidate for designing a robust polymer electrode membrane for electrochemical applications [7].…”
Section: Introductionmentioning
confidence: 99%
“…Another work by Paul et al [7] has shown that a novel MOF/Aquivion composite membrane exhibited enhanced proton conductivity compared with the Nafion. This material could be a promising candidate for designing a robust polymer electrode membrane for electrochemical applications [7]. There are several reviews were recently published on this important topic of proton conduction in MOFs [8][9][10].…”
Section: Introductionmentioning
confidence: 99%